Predicting recidivism: psychosocial collateral consequences among registered offenders. Issue 1 (2nd January 2023) - Hamilton, Emma; Fairfax-Columbo, Jaymes
ABSTRACT: The relationship between collateral consequences and recidivism among individuals who sexually offend continues to be proffered in the literature, yet empirical evidence of these links has yet to be established. This exploratory study investigated the correlational and predictive relationships between social and psychological collateral consequences and overall recidivism, sexual recidivism specifically, and probation/parole/registry violations among a sample of 180 registrants. Results revealed significant relationships between demographic indicators (age, years registered, education), social and psychological collateral consequences, overall recidivism, and sexual recidivism and violations. Results of the hierarchical logistic regressions indicated that neither social nor psychological collateral consequences significantly improved model fit for overall recidivism or sexual recidivism. Social collateral consequences, however, predicted an individual's likelihood to accrue probation, parole, or registry violations post-offence. Practical implications are discussed within the context of building an empirical basis for the potential contributory effects of the registry on recidivism, via collateral consequences.